Cardiovascular disease / Athifah Ismail and Ida Muryany Md Yasin - Ismail, Athifah; Md Yasin, Ida Muryany (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Cardiovascular disease (CVD) is associated with disorders of the heart and blood vessels consist of coronary heart disease, cerebrovascular disease, peripheral arterial disease, rheumatic disease, congenital heart disease, and deep vein thrombosis and pulmonary embolism (Blanchard & Miller, 1977; WHO, 2019; NHS, 2022). Symptoms of CVD eventually started from having chest pain or angina; then severe cases lead to heart attack or myocardial infarction (Kunnen & Van Eck, 2012; Jeong et al., 2018). Major causes of these phenomenon are due to the build-up of plaque around blood vessels which caused serious blockages in coronary artery, blood supply, limb arteries, and wall of the aorta as shown in figure 1 (NHS, 2019). Early signs of lipid blockages around blood vessels must be taken seriously including chest pain (angina), shortness of breath, dizziness, and exhaustion (Basson, 2008). Since 2005, CVD was reported responsible for 30% of mortality cases around the world (Basson, 2008, Chan et al., 2021). Statistics on the cause of death in Malaysia reported ischaemic heart disease as the top five death cases since 2014 (Statistics on causes of death Malaysia, 2022). It was reported, CVD occurrence acquired 13.7% of 157, 251 mortality cases as stated in Figure 2 (Firus Khan et al., 2022).